Sociology of Law as an Analytical Tool: Measuring the Effectiveness of Law in the Social Dynamics of Society - Rizqia Kamila Zahra (Universitas Negeri Yogyakarta, 2026)
This study examines the sociology of law not merely as an empirical discipline, but as a critical normative-analytical tool to measure the effectiveness of statutory law within social dynamics. Traditional legal analysis often isolates statutory norms from societal realities, leading to rigid and ineffective regulations. Adopting a qualitative research design with a normative-evaluative approach, this research utilizes the sociology of law framework to assess how legal norms and principles articulate the actual experiences, behaviors, and perceptions of legal actors and citizens. The results indicate that legal effectiveness is fundamentally determined by the normative responsiveness of a regulation toward evolving social structures. By integrating sociological dimensions into normative analysis, this study demonstrates that the sociology of law serves as an essential instrument to evaluate systemic legislative gaps. Consequently, this research recommends that legislative bodies incorporate sociological-normative indicators during the drafting process to ensure that future legal products possess both analytical precision and social legitimacy.